Symmetry detection using frequency domain motion estimation techniques - Tzimiropoulos, Georgios; Argyriou, Vasileios; Stathaki, Tania (IEEE, 2008)
A frequency domain approach for the detection of symmetries in real images is presented. Our framework is based on recent state-of-the-art research where motion estimation techniques are employed to sequentially determine all the associated parameters. In particular, we introduce several modifications regarding the order of symmetry estimation and the detection of the axes of possible bilateral symmetry. Preliminary results demonstrate the efficiency of our approach.